New camptothecin derivatives for generalized oncological chemotherapy: Synthesis, stereochemistry and biology. (15th August 2021) - Naumczuk, Beata; Górecki, Marcin; Wiktorska, Katarzyna; Urbanowicz, Magdalena; Sitkowski, Jerzy; Lubelska, Katarzyna; Milczarek, Małgorzata; Bednarek, Elżbieta; Bocian, Wojciech; Kozerski, Lech
Graphical abstract: Abstract: Derivatives of SN38 were synthesized that were either monosubstituted at C-5 or C-9 or disubstituted at both C-5 and C-9. Substitution to C-5 led to the generation of pairs of diastereomers (2c-2 h) in a one-pot reaction and was readily separable by HPLC. The absolute configurations of C-5 were established by electronic circular dichroism experiments. Compounds were tested in vitro against human cancer cell lines as well as a normal cell line. The impact of compounds 2a–2j on cancer cells is significant and the IC50 values against the normal cell line are several times higher than that of SN38. Using the Mannich reaction we obtained a new innovative group of derivatives with unique biological properties that preserves the high cytotoxicity in cancer cells and eliminates the acute toxicity to non-neoplastic cells, which can be considered a breakthrough in chemotherapy with the use of topoisomerase I inhibitors from the camptothecin family.